NILAI-NILAI DEMOKRASI DALAM PELAKSANAAN PELAYANAN PUBLIK DI ERA PANDEMIK COVID-19 DI KOTA SAMARINDA - Enos Paselle; Chatas Teguh Prakoso; Tri Susilowati (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
This research is motivated by the widespread spread of the Covid-19 Virus in Samarinda City which has an impact on the government administration process, especially in public services which are ideally able to adapt to environmental changes. The implementation of public services during the Covid-19 pandemic underwent changes with the aim of preventing the spread of Covid-19 in the City of Samarinda. At this time several institutions in Samarinda limit the service process to the people of Samarinda City. Public services during the current Pendmi period experienced a decline in the implementation process. Several offices, such as the Office of Population and Civil Registration, the North Samarinda District Office, and the Office of Investment and One-Stop Integrated Services and other services reduce activities in public services. This study uses a descriptive qualitative research method. The analysis technique uses steps such as data collection, data reduction, data display, verification and confirmation of conclusions. Meanwhile, the credibility check technique used in this research is source triangulation technique. The results of the study show that during the Covid 19 pandemic in Samarinda City, the implementation of public services in Samarinda City still consistently pays attention to democratic values ​​for its citizens so that people get services. The meaning of these democratic values ​​can be observed in the aspects of accountability, responsibility and equality in services by government agencies in Samarinda City.